Explaining Reasons and Factors of Job Embeddedness: Mixed Research - Ahmad Khani; Jalil Delkhah; Ahmad Ali Khaef Alahi (مدیریت دولتی, 2018)
Objectives: The purpose of this study is to identify the reasons and factors that will improve the survival of employees in the organization. In other words, we seek the answer to the question “why don’t people leave their jobs for another destination?” For this purpose, this study uses the concept of job embeddedness to examine the factors affecting the survival of employees. Method: In this research, based on a qualitative approach to theme analysis, some semi-structured interviews were initially conducted with some of the managers and experts of the National Bank of Iran (mainly located in Tehran), and  five themes (factors) of job embeddedness were extracted based on the coding of the data. Subsequently, a questionnaire was developed about these factors and their sub-components and distributed among 300 employees of the National Bank of Iran. Results: Internal and external communication, separation anxiety, organization compatibility with the individual, comfort and relaxation of working with the organization, and satisfaction with the organization's current conditions are identified as the five factors affecting job embeddedness. Conclusion: The results of confirmatory factor analysis confirmed the five factors and the sub-components of job embeddedness (reasons for not leaving or staying in the organization), and Bonferroni test also described the convenience and relaxation of working with the organization as the most important aspect of job embeddedness.